Proverbial Wisdom From K-State’s First Book: How to run a successful selection committee and approach a meaningful first year common reading experience. - Coleman, Tara; Finch, Emily (My University, 2021)
Common reading programs provide first-year students with common experiences that facilitate their engagement in the academic and social domains of college life. The experience gives faculty and staff the opportunity to engage and connect with students inside and outside of the classroom, and allows them to model academic behavior and intellectual discussion. Providing students with a stepping stone to make connections, through a book and related programming, K-State students aren’t thrown into campus life and left to navigate and fend for themselves. Selected books often address difficult themes, and serve as effective tools in bridging cultural gaps, and addressing issues in inclusion, diversity, equity, and access proactively rather than retroactively. In this session, we will talk about the guiding principles that shape the success of K-State’s First Book. We talk about the program’s history, and then dive into the administrative considerations and guiding principles that shape each stage of the common reading selection process. We will discuss decision making principles on various topics including: membership, selection criteria, partnerships, programming, and evaluating outcomes. We will also provide recommendations based on our experience on how to administer a successful and diverse common reading program and a successful book selection process.
Keywords: First-year experience program; Common reading program; K-State first; K-State first book; Committee management; Administration